(untitled) (Voice of Teacher, 2024)
This study focuses on estimating recent fertility levels in Nepal across different caste/ethnic groups, employing various methods with a particular emphasis on the Arriaga method. The extensive data assessment and corrections of individual variables were undertaken to obtain optimal fertility estimates. The study identifies a strong indication of fertility decline in Nepal, supporting previous studies findings. The hypothetical inter-survey cohort is employed to estimate fertility levels from December 2000 to December 2010 using the logistic method. This study analyzing the census data from 2001 and 2011, the study reveals variations in Total Fertility Rate (TFR) values among different caste/ethnic groups. For instance, the Newar, Tarai Janajiti, and Madheshi Brahman exhibit lower TFR values compared to the national census, while Hill Janajati, Brahman/Chhetri, Madheshi Other Caste, Hill Dalit, Madhesi Dalit, Muslim, and Others Minor Caste show higher values. The study applies hypothetical inter-survey analysis, indicating that Muslim, Hill Janajati, Madhesi Dalit, Madheshi Other Caste, Hill Dalit, Madhesi Dalit, and Others Minor Caste are expected to have fertility rates exceeding replacement levels by 2031. In contrast, Newar, Tarai Janajiti, and Brahman/Chhetri are projected to have fertility rates below replacement levels. This study contributes valuable insights into fertility trends and disparities among caste/ethnic groups in Nepal, emphasizing the need for targeted interventions and policy considerations based on these variations.